Multi-course photodynamic therapy of basal cell skin cancer of the central face area (clinical study) - E. V. Filonenko; A. N. Urlova; Yu. V. Vakhabova; S. V. Medvedev; O. V. Matorin; N. I. Grigorievykh; A. D. Kaprin (Biomedical Photonics, 2020)
The results of an 11-year clinical observation and treatment of a patient with stage II basal cell carcinoma of the face (Т2N0M0) are presented. History of the illness is associated with a long (from 2001 to 2008) inadequate treatment, due to the incorrect diagnosis. After the proper diagnosis was established, from 2008 to 2019 at the Center for Laser and Photodynamic Diagnostics and Tumor Therapy of P.A. Herzen Moscow Oncology Research Center, the patient underwent organ-preserving treatment using the multi-course photodynamic therapy (PDT) and drug targeted therapy. In total, 23 courses of PDT were conducted with photosensitizers of the chlorin series and 5-aminolevulinic acid during this period. Since 2018, the patient is in the process of targeted drug treatment with Vismodegib. In the course of targeted drug treatment, a follow-up examination in 2019 revealed continued growth of the residual tumor, and another course of PDT was carried out. Throughout the observation period, the patient tolerated the treatment well, without complications, with a good quality of life and satisfactory cosmetic effect.